DIFFERENTIAL DIAGNOSIS AND GENETIC TESTING FOR DETERMINING THE MOLECULAR CAUSES UNDERLYING ORO-DENTAL ANOMALIES IN A SERIES OF PATIENTS - Viorica Radoi; Andrei Kozma; Vasilica Toma; Horia Lăzărescu; Radu Ursu; Agnes Katherine Lackner; Laurențiu Camil Bohîlțea; Norina Forna (Romanian Society of Oral Rehabilitation, 2019)
Progress in genetics and molecular biology has resulted in the emergence of new concepts to explain the etiology and pathogenesis of many human disease processes including oro-dental diseases. Recent advances in molecular aspects of odontogenesis indicate that the development of teeth is under strict genetic control. More than 300 genes are involved in determination of the position, number, and shape of the different types of teeth. Currently, there are more than 4,000 genetic disorders identified till date, of which orofacial syndromes form a considerable part. Genetic factors either in isolation or in combination with various environmental factors plays role in causation of these craniofacial anomalies. Early diagnosis is often crucial for the effective treatment of functional and developmental aspects. However, not all syndromes can be clinically identified early, especially in cases of absence of known family history. Moreover, the treatment of these patients is often complicated because of insufficient medical knowledge, and because of the dental and craniofacial developmental variations. The role of the team is crucial for the prevention, proper function, and craniofacial development which is often combined with orthognathic surgery. Clinical phenotyping together with genetic data and pathway information will ultimately pave the way for preventive strategies and therapeutic options in the future. This will improve the prognosis for better functional and aesthetic outcome for these patients and lead to a better quality of life, not only for the patients themselves but also for their families.